Analisis Tanggung Jawab Pemerintah Dalam Penyediaan Transportasi Laut Bagi Siswa SMP Antar Pulau Di Kecamatan Jemaja Barat, Kabupaten Kepulauan Anambas - Sella Oktapatika; Novi Winarti; Ardi Putra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the responsibility of the Anambas Islands Regency Government in providing sea transportation for junior high school students traveling between islands in West Jemaja District. The study is motivated by the geographical characteristics of the archipelagic region, where students continue to depend on community-owned boats due to the absence of government-provided school transportation. A qualitative descriptive method was employed using Helbert J. Spiro's theory of government responsibility, which includes the dimensions of obligation, accountability, and cause. Data were collected through observation, interviews, and documentation involving the Education Office, school principal, parents, and boat operators. The findings reveal that the government has not yet provided a dedicated sea transportation fleet for students. However, it has partially fulfilled its responsibility through budget support, cooperation with local boat owners, service supervision, and the provision of safety equipment. Nevertheless, the continuity of transportation services still depends on community-owned boats. Therefore, stronger government commitment is required to establish safe, effective, and sustainable sea transportation services to ensure equitable access to education in the archipelagic region.